Assessment of mental health literacy in patients with breast cancer. (June 2016) - Cheung, Yin Ting; Ong, Ying Ying; Ng, Terence; Tan, Yee Pin; Fan, Gilbert; Chan, Choi Wan; Molassiotis, Alex; Chan, Alexandre
Introduction: Psychosocial distress is often underdiagnosed and undertreated among breast cancer patients due to the poor recognition of the associated symptoms and inadequate knowledge of the treatments available. Objective: To evaluate the mental health literacy of breast cancer patients by assessing (1) their ability to recognize the symptoms of anxiety, fatigue, depression, and cognitive disturbances, and (2) their knowledge of help-seeking options and professional treatments. Methods: In this multi-center, cross-sectional study, early-stage breast cancer patients receiving chemotherapy underwent four assessments to measure their levels of anxiety, depression, fatigue, and cognitive disturbances. With the aid of cancer-specific vignettes, a questionnaire was administered to evaluate their mental health literacy. Results: Fifty-four patients were recruited (77.7% Chinese, aged 52.7 ± 8.5 years). Clinically significant anxiety (15.1%), fatigue (27.8%), and cognitive disturbances (25.9%) were more prevalent than depression (5.6%). Although the majority of the patients could recognize the symptoms of fatigue accurately (75.9%), less than half could identify those of anxiety (35.2%), depression (48.1%), and cognitive disturbances (48.1%). Patients were more receptive to help from their family members (score: 3.39 out of 4.00) and oncologists (score: 3.13) than from other mental health specialists, such as psychiatrists (score: 2.26) and psychologists (score: 2.19) in the management of their psychosocial distress. Approximately half of the patients indicated that embarrassment and fear were their main barriers to seeking professional treatment (55.6%). Conclusions: Our results suggest that the mental health literacy of breast cancer patients was inadequate. Intervention and management strategies could be implemented to teach these patients about evidence-based treatments and professional help that are specific to mental disorders.